Hybrid Gel as a Substitute for Hard Fats in Confectionery - Vasilissa S. Kutsenkova; Nataliia V. Nepovinnykh; Samira A. Yeganehzad (Техника и технология пищевых производств)
The World Health Organization recommends reducing the intake of saturated fatty acids. However, a direct replacement of solid fats with liquid oils affects the technological and consumer properties of food. The research objective was to develop a hybrid gel with a dense structure based on oleogel and hydrogel to replace saturated fats in semi-finished confectionery products. The study featured samples of oleogel from sunflower oil and beeswax at a concentration of 10, 15, and 20% and hybrid gels prepared by mixing the oleogel with a 2% aqueous solution of sodium alginate at ratios of 99:1, 95:5, and 90:10. The samples were tested for strength, adhesive power, viscosity index, consistency, and Young modulus using a TA-XT Plus texture analyzer (Stable Micro Systems Ltd., UK). The water activity was studied using a water activity analyzer LabMaster (Novasina, Lab Master, Switzerland). The oleogel samples with wax concentrations of 20 and 15% demonstrated good adhesive strength. The best hybrid gel was the oleogel with 20% wax at the ratio of 95:5 to hydrogel. This ratio resulted in a considerable gel strength (≤ 408.222) while maintaining a dense and uniform texture (Young modulus ≤ 17.05) for a long time. The oleogels had low moisture content (Aw = 0.6 ± 0). The shelf life at 4–10°C was 6 months. The samples had good sensory properties, i.e., clear taste and smell, strong uniform structure and consistency, etc. The paper introduces a formulation for a semi-finished confectionery product with a hybrid gel instead of 30% cocoa butter substitute. Hybrid gels can be recommended as a substitute for cocoa butter or confectionery fats to reduce the amount of saturated and trans fatty acids. Such a replacement improves the consumer properties of semi-finished and finished products.